2010
DOI: 10.1038/eye.2010.124
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Heidelberg Retina Tomograph-I and -II in detecting glaucomatous changes using topographic change analysis

Abstract: Purpose To evaluate the suitability of including both Heidelberg Retina Tomograph-I (HRT-I) and HRT-II examinations in the same longitudinal series for HRT topographic change analysis (TCA) and to evaluate parabolic error correction (PEC) to improve the agreement between HRT-I and HRT-II examinations. Methods A total of 66 eyes from the University of California San Diego Diagnostic Innovations in Glaucoma Study with baseline HRT-I and HRT-II examinations obtained on the same day and Z3 HRT-II follow-up examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 20 publications
1
12
0
2
Order By: Relevance
“…In the latest HRT software version (HRT 3), the alignment algorithm corrects for horizontal and vertical shifts, rotational and tilt misalignment, and differences in parabolic distortion [known as parabolic error correction (PEC)], between baseline and each follow-up topography in a longitudinal series. Because the field of view of HRT Classic imaging is smaller than that of HRT II imaging, PEC is not applied when an HRT Classic examination is included in the longitudinal series 24. In the image alignment algorithm between HRT II topographic images only, the HEE software performs a parabolic correction to account for the curved surface of the peripapillary retina.…”
Section: Discussionmentioning
confidence: 99%
“…In the latest HRT software version (HRT 3), the alignment algorithm corrects for horizontal and vertical shifts, rotational and tilt misalignment, and differences in parabolic distortion [known as parabolic error correction (PEC)], between baseline and each follow-up topography in a longitudinal series. Because the field of view of HRT Classic imaging is smaller than that of HRT II imaging, PEC is not applied when an HRT Classic examination is included in the longitudinal series 24. In the image alignment algorithm between HRT II topographic images only, the HEE software performs a parabolic correction to account for the curved surface of the peripapillary retina.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the sources of parabolic error in HRT exams and the parabolic error correction procedure currently available in the HRT software are presented elsewhere 6. In brief, when the eye being imaged is at an optimal distance of 10mm from the HRT, the focal plane of the HRT lies parallel to the retinal surface and therefore, the HRT images are optimal without any distortion.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the current HRT software does not correct for differences in parabolic distortion between exams when there is at least one 10° HRT-I exam in a longitudinal series of topographies. Longitudinal study of HRT topographies with an HRT-I exam at baseline using HRT topographic change analysis (TCA) has shown that differences in parabolic distortion between HRT-I and HRT-II exams of each participant need to be corrected to provide good agreement between the TCA change parameters estimated from a longitudinal series with both HRT-I and HRT-II exams 6. In addition, a modified parabolic error correction procedure was proposed to improve the accuracy of the parabolic error correction for both between 2 HRT-II exams and between an HRT-I exam and an HRT-II exam to minimize the influence of deeper optic disk measurements on the parabolic error estimate and to adjust the parabolic error correction based on the imaging area.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations